Psychometric Properties of Sensory Processing and Self-Regulation Checklist (SPSRC) - Cynthia Y. Y. Lai; Trevor W. K. Yung; Ivan N. B. Gomez; Andrew M. H. Siu (Hindawi-Wiley, 2019)
Background. Some children may encounter difficulties in processing sensory stimuli, which may affect their ability to participate in activities of daily living. Self-regulation abilities may also affect children on how to process different sensory experiences. The Sensory Processing and Self-Regulation Checklist (SPSRC) was developed as a single, parent-reported instrument for the examination of sensory processing and self-regulation difficulties in children. Aims. This study is aimed at evaluating the psychometric properties of the SPSRC and examine the patterns of self-regulation and sensory processing in children with and without autism spectrum disorder (ASD). Methods and Procedures. The contents of the SPSRC were validated by a group of experts, and a field test was subsequently conducted to examine the reliability and validity of this instrument in a sample of 997 typically developing children and 78 children with ASD. Outcomes and Results. The results of the validation and field test analyses suggest that the SPSRC exhibits high internal consistency, good intrarater reliability, and a valid ability to measure and discriminate sensory processing and self-regulation in children aged 3-8 years with and without ASD. Conclusions and Implications. The current results supported the reliability and validity of SPSRC to assess a child's sensory processing and self-regulation performance in activities of daily living. The study findings warrant further investigation to compare the performance of the SPSRC with laboratory-based tests, as this would better elucidate sensory responsivity in children with sensory modulation disorders from both clinical and research perspectives.